2015
DOI: 10.1007/s00726-015-2015-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum and cerebrospinal fluid concentrations of homoarginine, arginine, asymmetric and symmetric dimethylarginine, nitrite and nitrate in patients with multiple sclerosis and neuromyelitis optica

Abstract: The pathogenic hallmarks of multiple sclerosis (MS) and neuromyelitis optica (NMO) are cellular and humoral inflammatory infiltrates and subsequent demyelination, or astrocytic cell death in NMO, respectively. These processes are accompanied by disruption of the blood-brain barrier as regularly observed by gadolinium enhancement on magnetic resonance imaging. The role of the L-arginine/nitric oxide (NO) pathway in the pathophysiology of neuroinflammatory diseases, such as MS and NMO, remains unclear. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
0
20
2
Order By: Relevance
“…These included the acylcarnitines:tetradecanoylcarnitine (AC (14:0)) and octadecanoylcarnitine (AC (18:0)), and biogenic amines: ADMA, nitrotyrosine, putrescine, symmetric dimethylarginine (SDMA), spermidine and trans-4-hydroxyproline. Asymmetric dimethylarginine was especially interesting The mean concentrations, standard deviations, concentration ranges and the number of samples in which the metabolites were detected are presented, as well as reference values from (Mandal et al 2012) and the CSF metabolome database (Wishart et al 2008 as it was significantly elevated in SPMS patients compared to controls, which previously has been shown to also be the case in comparison to other neurological diseases (Haghikia et al 2015). The concentrations of metabolites measured using relative one-point calibration are not discussed any further at this point since this cannot be considered a reliable measure of quantification.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These included the acylcarnitines:tetradecanoylcarnitine (AC (14:0)) and octadecanoylcarnitine (AC (18:0)), and biogenic amines: ADMA, nitrotyrosine, putrescine, symmetric dimethylarginine (SDMA), spermidine and trans-4-hydroxyproline. Asymmetric dimethylarginine was especially interesting The mean concentrations, standard deviations, concentration ranges and the number of samples in which the metabolites were detected are presented, as well as reference values from (Mandal et al 2012) and the CSF metabolome database (Wishart et al 2008 as it was significantly elevated in SPMS patients compared to controls, which previously has been shown to also be the case in comparison to other neurological diseases (Haghikia et al 2015). The concentrations of metabolites measured using relative one-point calibration are not discussed any further at this point since this cannot be considered a reliable measure of quantification.…”
Section: Discussionmentioning
confidence: 95%
“…Glycine, asymmetric dimethylarginine, PC-O (34:0) and hexoses were all significantly elevated in SPMS patients compared with controls. Elevated glycine levels in CSF have previously been observed in multiple sclerosis patients, possibly due to oxidative stress (Ďurfinová et al 2018;Haghikia et al 2015), whereas altered hexose/glucose metabolism could potentially be of importance for multiple sclerosis as it has been implicated in other neurodegenerative disorders (Pathak et al 2013). The increased levels of the glycerophospholipid PC-O (34:0) in SPMS patients has to our knowledge not been demonstrated previously, but altered levels of lipid composition in multiple sclerosis patients has recently been found in other cohorts of patients also (Nogueras et al 2019;Pathak et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most noteworthy is Tavazzi et al's study [16] of a large cohort of 113 RRMS patients in whom serum tNOx levels were significantly higher (p<0.001) in RRMS patients than in health controls. Three studies described no significant difference but were heterogeneous as to the MS disease phenotype, and none considered patients following an acute relapse [24][25][26]. A single study [27] found the opposite: significantly lower mean tNOx in RRMS patients compared to control groups; no significant study characteristics were identified to explain this disparity.…”
Section: Peripheral Bloodmentioning
confidence: 93%
“…In one study, mean CSF tNOx was significantly higher in RRMS than SPMS groups [33], supporting a role for tNOx as a marker of inflammatory disease activity. Two studies described no significant difference in CSF tNOx between MS and control groups but neither offered details on the disease activity of their patient populations [24,26]; case-mix differences may account for the disparity in the outcomes of these studies. Overall, there is good evidence for tNOx as a diagnostic marker in MS, particularly in acute MS relapse.…”
Section: Csfmentioning
confidence: 99%
“…ADMA is elevated by native or oxidized LDL and interferes with L-arginine in the production of nitric oxide (NO) [ 215 ]. Significantly higher ADMA concentrations were observed in serum and CSF of patients with RRMS and SPMS, while levels of arginine, L-homoarginine, nitrate, nitrite, ADMA did not differ between patients with MS and healthy controls [ 76 ] ( Table 3 and Table 4 ).…”
Section: Degradation Products Under Oxidative Stressmentioning
confidence: 99%